2020
DOI: 10.2147/ott.s218004
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of Gut Microbiome in Human Colorectal Cancer in Paired Tumor and Adjacent Normal Tissues</p>

Abstract: Background: To understand the biological effect of gut microbiome on the progression of colorectal cancer (CRC), we sequenced the V3-V4 region of the 16S rRNA gene to illustrate the overall structure of microbiota in the CRC patients. Methods: In this study, a total of 66 CRC patients were dichotomized into different groups based on the following characteristics: paired tumor and adjacent normal tissues, distal and proximal CRC segments, MMR (-) and MMR (+), different TNM staging and clinic tumor staging. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 37 publications
4
30
2
3
Order By: Relevance
“…Fn has been recently identified as a pathogenic bacteria in CRC (38). Additionally, the present study reported that the levels of Fn were increased in tumor tissues compared with in adjacent normal tissues of the same patients, supporting the authors' previous study (39), which revealed its role in promoting the initiation and development of CRC. Future investigations with a larger number of patients are required to determine the effects of Fn .…”
Section: Discussionsupporting
confidence: 92%
“…Fn has been recently identified as a pathogenic bacteria in CRC (38). Additionally, the present study reported that the levels of Fn were increased in tumor tissues compared with in adjacent normal tissues of the same patients, supporting the authors' previous study (39), which revealed its role in promoting the initiation and development of CRC. Future investigations with a larger number of patients are required to determine the effects of Fn .…”
Section: Discussionsupporting
confidence: 92%
“…These results are further supported by a number of recent studies [39][40][41][42][43][44][45][46][47]. For example, Sheng and coworkers [39] found the pathway of porphyrin and chlorophyll metabolism to be significantly altered in CRC patients, the perturbation is also validated in literature [40] by the genes from the pathway. Purines are basic components of nucleotides in cell proliferation, thus impaired purine metabolism has been associated with the progression of cancer [41,42].…”
Section: ) Key Pathways Identified By Differential Msan Networksupporting
confidence: 55%
“…The link between dysbiosis and colorectal cancer (CRC) is the most extensively studied. One major indication of association between microbiota alteration and cancer was the observation that the bacterial composition and diversity of tumours was significantly different than that of adjacent normal tissue [50][51][52][53][54][55]. Intriguingly, tumour-associated bacteria included strains known to impair anticancer immune responses and induce a chronic inflammatory state, such as Fusobacterium nucleatum [56] and Bacteroides fragilis [57,58], respectively.…”
Section: Dysbiosis Impairs Immune Function and Promotes Cancer Develomentioning
confidence: 99%